Estudo de níveis de farinha da vagem de algaroba (Prosopis juliflora (SW) D. C.) em rações para suínos na fase de terminação - Evangelista, José Nailton Bezerra (1990)
Forty eight crossbreed pigs of both sexes,weighing an average 62.400kg, were used in a randomized blocks design to evaluate the effects of diets'containing different-levels of algaroba (Prosopis juliflora (SW) D.C.) on pigs perfomance and on characteristics of the carcass [...]